Fungsi Badan Permusyawaratan Desa (BPD) Dalam Penyelengaraan Pemerintah Di Desa Botuh Bosi Kecamatan Simpang Hulu Kabupaten Ketapang - Putri, Cris Egita; Yohanes, Yulius; Sujendra, Bima (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This research is intended to examine the Function of the Village Consultative Body (BPD) in Village Government Administration in Botuh Bosi Village, Simpang Hulu District, Ketapang Regency in 2024. The researcher's motivation for conducting this study stems from the supervisory function that remains suboptimal in carrying out oversight activities. The type of research employed is descriptive research with a qualitative approach. This study utilizes interview and documentation data collection methods, applying the Supervisory Process theory to establish standards, measure implementation, compare implementation with standards, and correct deviations as proposed by G.R. Terry (Sukma, 1992:16). The research findings are as follows: 1) Establishing Standards - in determining standards, the Botuh Bosi Village government has adhered to laws and government regulations concerning villages; 2) Measuring Implementation - in the implementation at Botuh Bosi Village, this is assessed through APBDes (Village Revenue and Expenditure Budget) implementation benchmarks, community satisfaction levels, and degree of community involvement; 3) Comparing Implementation with Standards - in this regard, the government conducts evaluations to determine whether the implementation conforms to existing standards; 4) Correcting Deviations - the correction of deviations in Botuh Bosi Village aims to ensure that no deviations occur in the execution of respective functions and duties.